1976
DOI: 10.1002/aic.690220218
|View full text |Cite
|
Sign up to set email alerts
|

Axial distribution of reactivity inside a fluid‐bed contactor

Abstract: The axial distribution of reactivity inside a fluid-bed contactor is studied for the hydrogenation of ethylene. The reactivity is large near the surface of the dense phase. The significant effect of the dilute phase, or the free board region, is verified experimentally, and the contact efficiency in the transition zone and in the dilute phase is obtained. The contact efficiency was approximated by T~ = 1 -0.75(c,/~,d~)O.~. The temperature rise in the dilute phase is measured in the small reactor. The transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The LGG plot gives the value of kebab and the fraction of directcontact-catalyst. The effect of the bed diameter on these parameters is discussed and compared with previous experimental results (Lewis et al, 1959;van Swaaij and Zuiderweg, 1972;Furusaki et al, 1976;Miyauchi et al, 1980;Nozaki et al, 1984).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The LGG plot gives the value of kebab and the fraction of directcontact-catalyst. The effect of the bed diameter on these parameters is discussed and compared with previous experimental results (Lewis et al, 1959;van Swaaij and Zuiderweg, 1972;Furusaki et al, 1976;Miyauchi et al, 1980;Nozaki et al, 1984).…”
mentioning
confidence: 70%
“…Miyauchi (1974a) has noticed that the effect of the catalyst particles in the freeboard is significant in comparison with the overall reactivity of the bed. Furusaki et al (1976) and Miyauchi et al (1980) gave experimental results on the change of reactivity in the longitudinal direction including the effect of the freeboard. By examining their results it was found that besides the mass transfer coefficient the fraction of direct-contact-catalyst was important in controlling the reaction in fluid beds.…”
mentioning
confidence: 99%
“…This phenomenon was taken into account by the use of a contact efficiency parameter,  g-s , between gas and solids in the freeboard, calculated by the equation proposed by Furusaki [19] 0.4…”
Section: Fluid Dynamics In the Freeboardmentioning
confidence: 99%
“…Recent experimental work (Chavarie and Grace 1975, Furusaki et al 1976, Ford et al 1977, Pereira and Beer 1978 shows the need to consider regions other than the bubbling bed in modeling fluidized bed reactors. Behie and Kehoe (1973) modeled the grid jet entry region at the bottom of fluidized beds.…”
Section: Conclusion and Significancementioning
confidence: 99%